KESANTUNAN GURU DAN SISWA PEREMPUAN DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH BILINGUAL - Rosinawati Dewi; Sarwiji Suwandi; Edy Tri Sulistyo (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The purposes of this study are to explain (1) the form of politeness principles by language teacher languages and female students in the learning process of Indonesian language at SMA Al Abidin Bilingual Boarding School (SMA ABBS), (2) violation to politeness principle of female teachers and female students in learning process of Indonesian learning in SMA ABBS.  Using qualitative approach, this study assigned the 2nd graders of SMA ABBS as the research subjet. Data were collected using recording techniques. Validity in this study was examined using method triangulation. Results of this study show five varieties of politeness principles including maxim of tact, generousity, praise, humanity and consciousness and the violations of the five maxims do occur in learning process of Indonesian language among teachers and female students.